Balance of Payments Disequilibriumin and Implication for Economic Growth in Nigeria - M., Pamogho,; E. P., Ifionu,; S. S., Ogunbiyi, (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This study examined the impact of Balance of Payments Disequilibriumin And Implication for Economic Growth in Nigeria over the time frame of 1981 to 2020. Secondary data were sourced from Central Bank of Nigeria statistical bulletin of various issues and CBN annual reports. In analyzing the short and long-run dynamic relationship between Gross Domestic Product and selected Balance of Payment determinants which include; Balance of Payment and Exchange rate. This study utilized the Unit root test, Ordinary Least Square method, Granger Causality and Generalized Autoregressive Conditional Heteroskedasticity (GARCH) in capturing the short-run and volatility dynamics of the variables used in the model. The result revealed the existence of negative and insignificant relationship between Balance of Payment and Gross Domestic Product proxy for Economic growth while Exchange rate exhibited negative and significant relationship on economic growth in Nigeria. The study therefore recommends that Balance of payments position in Nigeria constitutes a structural problem that can hinder the attainment of potential growth. It has been shown clearly that, these problems can be addressed by diversifying the structure of production; reduce dependency on imports, making exports competitive in the international markets through macroeconomic stability, improvement in the state of infrastructure, human capital development, and eradication of corruption. Also, Government should create an incentive that would encourage investment in the country and also improve the balance of payments position.